Dual-band bandstop filter based on predistortion hybrid reflection function - Socheatra, S. (Institute of Electrical and Electronics Engineers Inc., 2017)
This paper presents an approach to realize a dual-band microwave bandstop filter based on predistortion reflection mode of a hybrid filtering function. A product of any two suitable classical filtering functions either from the same or different classes can form a hybrid dual-band filtering functions. Under multi-stage predistortion reflection mode technique, the predistorted hybrid lowpass reflection function can be synthesized using unified cascaded synthesis. This yields multiple lumped Brune sections and second order cross-coupled Brune sections to be extracted. To prove the synthesis, a 4th order hybrid Chebyshev and Butterworth filtering has been synthesized and simulated in Advanced System Design (ADS). © 2016 IEEE.